Potential of Bacterial Isolates from Peat Land as Controlling Agent for the Root Knot Nematodes Meloidogyne incognita - Elvina Efendi; Supramana; Giyanto (Jurnal Fitopatologi Indonesia, 2021)
Potential of Bacterial Isolates from Peat Land as Controlling Agent for the Root Knot Nematodes Meloidogyne incognita The root-knot nematodes (Meloidogyne spp.) is an important parasite of cultivated plants and have a wide host range. One of the potential alternative to controlling this pathogen is by utilizing non-pathogenic bacteria. This study aims to evaluate the potential of bacteria from peat as a biological control agent for the root-knot nematodes (M. incognita). In vitro testing was conducted by using filtrate of 15 bacterial isolates against M. incognita juvenile 2 (J2) in a 5 cm petri dish. Fivety juveniles (J2) of M. incognita were added to 4.5 mL of bacterial filtrate and incubated at 27 ℃. Nematode mortality was observed at 6, 12, and 24 hours after treatment. The experiment was arranged in a completely randomized design with three replications. The variables observed include the percentage of nematode mortality and the length of lethal exposure to nematodes. Physiological characterization test was carried out to the bacterial isolates including the production of HCN and chitinase enzymes. The results showed that nine bacterial isolates, that are GA2 GAA1, GT1 GTA7, GT1 GTB3, GT1 GTB4, GT1 GTB6, GT1 GTB7, GT1 GTC2, GT1 GTC4, and STDHC4 perform nematicidal activities with mortality level 83% to 94%. Three bacterial isolates, that are GT1 GTB4, GT1 GTB7, and GT1 GTC2 produce chitinase enzymes with lysis index above 1, but none of those isolates produce HCN. Bacterial isolates GT1 GTB4 and GT1 GTB7 had 99% homology with Serratia marcescens from China, and GT1 GTC2 had 99% homology with Streptomyces sp. AT67 from South Korea.